Associations Between Adverse Childhood Experiences and Negative Sleep Health Among Young Adults - (:unkn) unknown (My University, 2020)
Poor sleep health has been marked as a major factor impacting young adults’ social, academic, and physical performance in a negative direction. Existing research has shown that stress related mental illness or disorder are significant risk factors that contribute to negative sleep health in a bidirectional relationship. Such stress can be contributed by stressors of daily life, as well as adverse experiences and other experiences from earlier in the development. Purpose of the current study aimed to contribute to the existing understanding of the mechanisms that connect early trauma and disadvantage to sleep difficulties in emerging adulthood. Results indicated that adverse childhood experiences/events (ACEs) were significantly negatively associated with current sleep health among young adults, and that these relationships are partially associated with emotional distress symptoms or levels as well. Thus, early ACEs can significantly contribute to impaired sleep health among young adults in the present, and emotional distress symptom could be one of the mechanisms contributing to this relationship among young adults.
Keywords: Adverse Childhood Experiences; emotional distress symptoms; sleep health